1994
DOI: 10.1177/001872089403600301
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Skill from a Computer Game Trainer to Flight

Abstract: An experimental study was conducted to test the transfer of skills from a complex computer game to the flight performance of cadets in the Israeli Air Force flight school. The context relevance of the game to flight was argued on the basis of a skill-oriented task analysis, using the framework provided by contemporary models of the human processing system. The influence of two embedded training strategies was compared, one focusing on the specific skills involved in performing the game, the other designed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(202 citation statements)
references
References 18 publications
(19 reference statements)
10
189
0
3
Order By: Relevance
“…The measurement of the attention as a predictor of flight performance was previously shown in several works [2], [3] and theoretical and empirical evidence exists in support of the argument that the control of attention and the ability to establish better attention-management can develop with training [4].…”
Section: Introductionmentioning
confidence: 66%
“…The measurement of the attention as a predictor of flight performance was previously shown in several works [2], [3] and theoretical and empirical evidence exists in support of the argument that the control of attention and the ability to establish better attention-management can develop with training [4].…”
Section: Introductionmentioning
confidence: 66%
“…Fortunately, innovative research funded by the Israeli Air Force offers some promise in addressing this issue. Gopher, Weil, and Bareket (1994) developed a computer game to help train Israeli Air Force cadets before flight training. The computer game simulation was not high fidelity and did not stress motor skills; instead, the game emphasized the higher level conceptual skills (such as the ones identified in the JASS for the experienced EPs) necessary to anticipate and plan in a combat aviation environment.…”
Section: Discussionmentioning
confidence: 99%
“…Schaie 1986, Willis et al 2006) while some reports showed also transfer effects upon non-trained activities (e.g. Ball et al 2007;Cassavaugh and Kramer 2009;Caserta et al 2007;Edwards et al 2009;Gopher et al 1994;Karbach and Kray 2009). However, this can also be due to an implicit involvement of non-explicitly trained functions in the trained function (see Kramer and Morrow 2008).…”
Section: General Factors Affecting Cognitive Functions In Agingmentioning
confidence: 99%